2006
DOI: 10.1002/j.2161-0029.2006.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Sensitive Dementia Caregiving Models and Clinical Practice

Abstract: Family caregiving for individuals with dementia is an increasingly complex issue that affects the caregivers' and care recipients' physical, mental, and emotional health. This article presents 3 key culturally sensitive caregiver models along with clinical interventions relevant for mental health counseling professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…It was identified as a culturally sensitive model for dementia care (Daire & Mitcham-Smith, 2006) and was found to predict caregiving consequences (Shyu & Lee, 2002). Similar findings were also reported in studies conducted in Western countries (Beach 1993;Carmack, 1997).…”
Section: Discussionsupporting
confidence: 60%
“…It was identified as a culturally sensitive model for dementia care (Daire & Mitcham-Smith, 2006) and was found to predict caregiving consequences (Shyu & Lee, 2002). Similar findings were also reported in studies conducted in Western countries (Beach 1993;Carmack, 1997).…”
Section: Discussionsupporting
confidence: 60%
“…It is recommended that counselors encourage caregivers to identify positive coping strategies, such as reading a book, taking a walk, cooking, doing arts and crafts, and spending time with friends and family, to maintain self‐care. As caregivers remain consistent with self‐care to manage caregiver stress, they are likely to experience success as caregivers (Daire & Mitcham‐Smith, ). Therefore, counselors should remind caregivers to take time for themselves and take breaks from caregiving as needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Schure et al () reported that caregivers feel responsible to provide care, and this feeling can lead to social isolation and burnout. Research has proven that caregivers’ particular situation and stressors typically dictate their coping strategies when faced with the caregiver role (Daire & Mitcham‐Smith, ). Therefore, professional counselors must be aware of the complex, multifaceted needs of the primary caregiver.…”
mentioning
confidence: 99%
“…For the purposes of this study, adult child caregivers are defined as the biological or adopted children of individuals diagnosed with dementia who provide care for such a parent and are engaged simultaneously in other coexisting family relationships with spouses, significant others or children. As primary caregivers, adult child caregivers often have total responsibility for care provision and safety of their parent (Daire & Mitcham-Smith, 2006).…”
Section: Adult Child Caregivermentioning
confidence: 99%
“…The adult child caregiver's responsibilities include but are not limited to attending to activities of daily living (ADLs) and ensuring medical treatments, care compliances, and welfare of their parents (Daire & Mitcham-Smith, 2006;Waldrop, 2007). Adult child caregivers often experience a reversal of role with the relative for whom they provide care (Che, Yeh, & Wu, 2006); they also have to balance caregiving with the other responsibilities in their lives, which include care of other family members, social engagements, and paid work (Daire & Mitcham-Smith, 2006).…”
Section: Adult Child Caregivermentioning
confidence: 99%